2018
DOI: 10.1029/2018je005570
|View full text |Cite
|
Sign up to set email alerts
|

The Far‐UV Albedo of Europa From HST Observations

Abstract: We present an analysis of Europa's far‐UV spectral albedo using observations during the 1999–2015 time period made by the Space Telescope Imaging Spectrograph on the Hubble Space Telescope. Disk‐integrated observations show that the far‐UV spectrum in the ~130 to 170‐nm range is relatively flat or slightly blue (increasing albedo with decreasing wavelength) for the studied hemispheres: the leading, trailing, and anti‐Jovian hemispheres. At Lyman‐α (121.6 nm), the albedo of the trailing hemisphere continues the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Figure 3b shows the 300 μm H 2 O reflectance spectrum scaled to Ganymede's leading hemisphere to indicate where Ganymede's FUV reflectance diverges from that of pure water ice. A potentially similar modification of the FUV water ice feature has been noted in UV HST/STIS observations of Europa (Becker et al, 2018), although Europa's reflectance in the 170–210 nm region has not yet been published and the exact FUV spectral shape therefore remains unclear.…”
Section: Ganymede's Fuv Reflectancesupporting
confidence: 66%
See 3 more Smart Citations
“…Figure 3b shows the 300 μm H 2 O reflectance spectrum scaled to Ganymede's leading hemisphere to indicate where Ganymede's FUV reflectance diverges from that of pure water ice. A potentially similar modification of the FUV water ice feature has been noted in UV HST/STIS observations of Europa (Becker et al, 2018), although Europa's reflectance in the 170–210 nm region has not yet been published and the exact FUV spectral shape therefore remains unclear.…”
Section: Ganymede's Fuv Reflectancesupporting
confidence: 66%
“…There are many materials we could add to darken the intraparticle models and fit Ganymede's near‐UV and visible reflectance, compared with only one method we have identified that may brighten the intimate model, and we cannot currently confirm that this method would work due to a lack of optical constants. Additionally, the water absorption edge is absent from the reflectance spectrum of Europa (Becker et al, 2018), and the Europan surface is thought to be considerably icier than Ganymede's. An improved silicate‐H 2 O intimate model may prove to be bright enough for Ganymede, but we anticipate that it will be difficult to identify silicates bright enough to reproduce Europa's visible reflectance, which is >0.7 at 500 nm (Spencer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory data on the spectral signatures of trace organics in ice, salts and acids is greatly lacking, and none that we know of covering the deep UV to 5 micron range of the Europa clipper mission. Also, puzzling is the lack of the ~165nm water absorption edge in the far-ultraviolet spectra as revealed by Hubble observations of Europa and Ganymede (Becker et al, 2018, Molyneux et al, 2020. What unique endogenic/exogenic processes are at play at Europa's top surface veneer that mutes this distinct water ice signature observed for many Saturnian satellites?…”
Section: Galileo and Europa Clipper Missions To The Jovian Systemmentioning
confidence: 99%